LINGUISTIC FEATURES OF UZBEK COMEDIES AND DEVICES OF HUMOR CREATION (SCIENCE TIME JOURNAL, 2026)
This article investigates the linguistic features of Uzbek comedies, the internal capabilities of the Uzbek language in creating the comedy genre, and the writer’s artistic mastery from both theoretical and practical perspectives. The study identifies the semantic scope and stylistic specificity of linguistic units in Uzbek comedies, as well as the syntactic means ensuring expressive impact.